Pengaruh Kinerja Keuangan dan Makro Ekonomi Terhadap Harga Saham - Ateu Nurcahyati; Nurdin (UNISBA Press, 2023)
Abstract. This study aims to determine and analyze (1) the financial and macroeconomic performance of the food and beverage sub-sector companies on the IDX in 2019-2020; (2) share prices in food and beverage sub-sector companies on the IDX in 2019-2020; (3) the effect of financial and macroeconomic performance on stock prices in food and beverage sub-sector companies on the Indonesia Stock Exchange in 2019-2020 either simultaneously or partially. The method used in this research is quantitative with descriptive and associative research types. The population in this study is the food and beverage sub-sector companies listed on the IDX in 2019-2021. The sampling technique used is purposive sampling, with a total sample of 25 companies. The analytical technique used in this research is multiple linear regression analysis. The results of the analysis show (1) the development of total asset turnover at Digital Banks in 2016-2020 tends to decrease every year; (2) the development of return on assets at Digital Banks in 2016-2020 tends to decrease every year; (3) the price book value development at Digital Banks in 2016-2020 tends to fluctuate; (4) Simultaneously return on equity, current ratio, debt to equity, earnings per share, and inflation have a significant effect on stock prices in food and beverage sub-sector companies on the IDX in 2019-2021. Partially, return on equity, debt to equity, earnings per share, and inflation have a significant effect on stock prices in food and beverage sub-sector companies on the IDX in 2019-2021, while the current ratio has no significant effect on stock prices in food and beverage sub-sector companies. drinks on the IDX in 2019-2021. Keywords: Financial Performance, Macroeconomics, Stock Prices, Covid-19 Pandemic Abstrak. Penelitian ini bertujuan mengetahui dan menganalisis (1) kinerja keuangan dan makro ekonomi pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2020; (2) harga saham pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2020; (3) pengaruh kinerja keuangan dan makro ekonomi terhadap harga saham pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2020 baik secara simultan maupun parsial. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan jenis penelitian deskriptif dan asosiatif. Populasi dalam penelitian ini adalah perusahaan sub sektor makanan dan minuman yang terdaftar di BEI Tahun 2019-2021. Teknik sampling yang digunakan adalah purposive sampling, dengan jumlah sampel penelitian sebanyak 25 perusahaan. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil analisis menunjukkan (1) perkembangan total asset turnover pada Bank Digital tahun 2016-2020 cenderung mengalami penurunan setiap tahunnya; (2) perkembangan return on asset pada Bank Digital tahun 2016-2020 cenderung mengalami penurunan setiap tahunnya; (3) perkembangan price book value pada Bank Digital tahun 2016-2020 cenderung fluktuatif; (4) secara simultan return on equity, current ratio, debt to equity, earning per share, dan inflasi berpengaruh signifikan terhadap harga saham pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2021. Secara parsial return on equity, debt to equity, earning per share, dan inflasi berpengaruh signifikan terhadap harga saham pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2021, sedangkan current ratio tidak berpengaruh signifikan terhadap harga saham pada perusahaan sub sektor makanan dan minuman di BEI Tahun 2019-2021. Kata Kunci: Kinerja Keuangan, Makro Ekonomi, Harga Saham, Pandemi Covid-19